Desulfurisasi Batubara Dengan Metode Leaching Menggunakan Naoh Dan HCL Di PT. Anugerah Krida Utama, Kutai Kartanegara, Kalimantan Timur - Widya Indriani; Tommy Trides; Windhu Nugroho (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The utilization of coal as a fossil fuel causes several ecological problems, as for the consequences of the coal combustion process, namely pollution and emissions. Combustion of high sulfur coal produces sulfur dioxide gas (SO2). This sulfur dioxide (SO2) will become H2SO4 (sulfuric acid) which can directly or indirectly disrupt human life, such as causing acid rain, causing tightness in the respiratory tract and causing corrosion and shortening the life of factory equipment. To reduce SO2 gas, a reduction in sulfur content is carried out before combustion which is called desulfurization. This research was conducted using the leaching method with variations in leaching agent and solution concentration. Leaching agents used in this study are NaOH and HCl. The coal to be desulfurized is coal from PT Anugerah Krida Utama with an initial total sulfur content of 4,05% adb. 10 grams of coal with a size of 0,212 mm was leached with 250 ml of chemical solution using a hot plate stirrer at 80˚C and 250 rpm for 1 hour. The results showed that the optimum condition for leaching agent NaOH occurred at a concentration of 8 M showing the initial total sulfur content of 4,05% adb decreased to 1,69% adb with a maximum percentage decrease of 58,27% and at leaching agent HCl the optimum condition occurred at a concentration of 1 M showing the initial total sulfur content of 4,05% adb decreased to 2,91% adb with a maximum percentage decrease of 28,14%.